Rekonstruksi Paradigma Kepemimpinan Pendidikan Islam Kontemporer melalui Integrasi Teori Transformasional dan Nilai Profetik - Fresyam Antika Ajeng (PT. Panca Publishing Indonesia, 2026)
This study aims to reconstruct the paradigm of contemporary Islamic educational leadership through the integration of transformational leadership theory and prophetic values. The research addresses the epistemological gap between the dominant transformational leadership model, which is largely rooted in rational-empirical traditions, and the moral-transcendental foundation of Islamic education. A qualitative Systematic Literature Review was conducted using the PRISMA protocol, covering national and international publications from 2015 to 2025 indexed in Scopus, Web of Science, ERIC, Google Scholar, Garuda, and Sinta. Data were analyzed using thematic narrative synthesis with a philosophical-integrative approach. The findings indicate that transformational leadership developed by James MacGregor Burns and Bernard M. Bass remains effective in promoting vision, innovation, and organizational commitment, yet requires explicit moral grounding in Islamic contexts. Meanwhile, prophetic leadership values influenced by Kuntowijoyo provide ethical and transcendental orientation but lack systematic integration with modern leadership theory. This study formulates the Integrative Transformational-Prophetic Leadership Paradigm (KTPI), emphasizing moral integrity, visionary inspiration, adaptive innovation, humanization-empowerment, and transcendence orientation. The model contributes theoretically by offering a dialogical epistemological synthesis and practically by providing a conceptual framework for Islamic educational institutions in responding to contemporary global challenges.